Перспективи розвитку сталого туризму в Україні: виклики та можливості - Панасюра, Вікторія Миколаївна; Panasiura, V. M. (Харків : Харківський національний університет імені В. Н. Каразіна, 2025)
Досліджено теоретичні основи розвитку сталого туризму, розглянуто визначення, поняття та принципи, представлено методичні основи дослідження формування показників оцінки сталого розвитку туризму та опрацьовано закордонний досвід реалізації його принципів. Проведено аналіз сучасного стану туризму в Україні, досліджено проблеми розвитку сталого туризму в умовах війни та запропоновано перспективні напрями забезпечення розвитку напряму в Україні.

The theoretical foundations of sustainable tourism development have been explored, including definitions, concepts, and principles. The methodological framework for evaluating sustainable tourism indicators is presented, along with a review of international experience in implementing sustainability principles. An analysis of the current state of tourism in Ukraine was conducted. The study examined the challenges of developing sustainable tourism under wartime conditions and proposed promising directions to ensure its development in Ukraine.
Prospects for the development of sustainable tourism in Ukraine: challenges and opportunities
Керівник: Волкова Ірина Ігорівна, старший викладач кафедри світової політики, дипломатії та туристичного бізнесу
Keywords: SOCIAL SCIENCES::Social sciences::Political science; SOCIAL SCIENCES::Business and economics; SOCIAL SCIENCES::Other social sciences::Public sector research; SOCIAL SCIENCES::Other social sciences::European research cooperation; сталий туризм; розвиток туризму; принципи сталості; оцінка сталого розвитку; війна в Україні; туристична галузь; стратегія розвитку; туристична стійкість; sustainable tourism; tourism development; sustainability principles; sustainability assessment; war in Ukraine; tourism sector; development strategy; tourism resilience; INTERDISCIPLINARY RESEARCH AREAS::Cultural heritage and cultural production